Effectiveness of durian peel ethanol extract for lowering blood sugar levels in alloxan diabetic wistar rats - Budi, Andre; Nababan, Samuel Maringan Tua; Nardi, Leo (Jurnal Prima Medika Sains, 2023)
High blood sugar levels can be influenced by several factors, including high-carbohydrate food consumption and a lack of physical activity. To minimize the side effects of hyperglycemic treatment, efforts have been made to explore anti-hyperglycemic compounds from other sources, such as durian peel (Durio zibetthinus Murr.). This study aimed to determine the effectiveness of ethanol extract from durian peel in lowering alloxan-induced blood sugar levels in Wistar rats (Rattus novergicus). The study is an experimental research employing an alloxan-induced diabetic rat model. The rats were divided into five different groups: Group I (negative control), Group II (positive control), Group III (dose 25 × 10–30/gBW), Group IV (dose 50 × 10–30/gBW), and Group V (dose 100 × 10–30/gBW). The durian peel used in this study was extracted using the maceration method with ethanol as the solvent. The results of this study indicate that ethanol extract from durian peel significantly reduced blood sugar levels after 10 to 15 days of durian peel extract administration (p < 0.05).